Differences in Intracellular Fate of Two Spotted Fever Group Rickettsia in Macrophage-Like Cells - Curto, Pedro; Simões, Isaura; Riley, Sean P.; Martinez, Juan J. (Frontiers in Cellular and Infection Microbiology, 2016)
Spotted fever group (SFG) rickettsiae are recognized as important agents of human tick-borne diseases worldwide, such as Mediterranean spotted fever (Rickettsia conorii) and Rocky Mountain spotted fever (Rickettsia rickettsii). Recent studies in several animal models have provided evidence of non-endothelial parasitism by pathogenic SFG Rickettsia species, suggesting that the interaction of rickettsiae with cells other than the endothelium may play an important role in pathogenesis of rickettsial diseases. These studies raise the hypothesis that the role of macrophages in rickettsial pathogenesis may have been underappreciated. Herein, we evaluated the ability of two SFG rickettsial species, R. conorii (a recognized human pathogen) and Rickettsia montanensis (a non-virulent member of SFG) to proliferate in THP-1 macrophage-like cells, or within non-phagocytic cell lines. Our results demonstrate that R. conorii was able to survive and proliferate in both phagocytic and epithelial cells in vitro. In contrast, R. montanensis was able to grow in non-phagocytic cells, but was drastically compromised in the ability to proliferate within both undifferentiated and PMA-differentiated THP-1 cells. Interestingly, association assays revealed that R. montanensis was defective in binding to THP-1-derived macrophages; however, the invasion of the bacteria that are able to adhere did not appear to be affected. We have also demonstrated that R. montanensis which entered into THP-1-derived macrophages were rapidly destroyed and partially co-localized with LAMP-2 and cathepsin D, two markers of lysosomal compartments. In contrast, R. conorii was present as intact bacteria and free in the cytoplasm in both cell types. These findings suggest that a phenotypic difference between a non-pathogenic and a pathogenic SFG member lies in their respective ability to proliferate in macrophage-like cells, and may provide an explanation as to why certain SFG rickettsial species are not associated with disease in mammals.